MEASURING THE IMPACT OF ZAKAT DISTRIBUTION ON ECONOMIC INEQUALITY: A META-ANALYSIS APPROACH - Mujahidin (Referensi Islamika: Jurnal Studi Islam, 2024)
This study aims to examine and measure the impact of zakat distribution on economic inequality, addressing the lack of comprehensive integration among diverse empirical findings. Given the persistent issue of inequality in Muslim-majority developing countries, this research highlights the relevance of zakat as a strategic Islamic social finance instrument for wealth redistribution. The study employs a systematic literature review (SLR) combined with a narrative meta-analysis of empirical studies published between 2015 and 2026, analyzing relevant works to identify patterns, approaches, and outcomes related to zakat distribution and its effects on economic inequality. The findings reveal that zakat contributes significantly to reducing economic inequality at a moderate level, primarily through increasing the income of mustahik (zakat beneficiaries) and strengthening microeconomic activities. However, its effectiveness in addressing long-term structural inequality is highly dependent on governance quality, distribution models, and alignment with public policy frameworks. This study is limited by its reliance on secondary data and variations in measurement approaches across the reviewed studies, which may affect generalizability. Nevertheless, it offers practical implications for policymakers and zakat institutions to improve governance, optimize distribution strategies, and enhance integration with broader economic policies. Furthermore, this research provides a novel contribution by proposing an outcome-based integrative model that connects consumptive zakat, productive zakat, digitalization, and multidimensional inequality indicators, offering a more comprehensive framework for understanding and optimizing the role of zakat in reducing economic inequality. This study aims to examine and measure the impact of zakat distribution on economic inequality, addressing the lack of comprehensive integration among diverse empirical findings. Given the persistent issue of inequality in Muslim-majority developing countries, this research highlights the relevance of zakat as a strategic Islamic social finance instrument for wealth redistribution. The study employs a systematic literature review (SLR) combined with a narrative meta-analysis of empirical studies published between 2015 and 2026, analyzing relevant works to identify patterns, approaches, and outcomes related to zakat distribution and its effects on economic inequality. The findings reveal that zakat contributes significantly to reducing economic inequality at a moderate level, primarily through increasing the income of mustahik (zakat beneficiaries) and strengthening microeconomic activities. However, its effectiveness in addressing long-term structural inequality is highly dependent on governance quality, distribution models, and alignment with public policy frameworks. This study is limited by its reliance on secondary data and variations in measurement approaches across the reviewed studies, which may affect generalizability. Nevertheless, it offers practical implications for policymakers and zakat institutions to improve governance, optimize distribution strategies, and enhance integration with broader economic policies. Furthermore, this research provides a novel contribution by proposing an outcome-based integrative model that connects consumptive zakat, productive zakat, digitalization, and multidimensional inequality indicators, offering a more comprehensive framework for understanding and optimizing the role of zakat in reducing economic inequality.